2013
DOI: 10.1093/jac/dkt418
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in penicillin-binding protein genes in clinical Staphylococcus aureus isolates that are methicillin resistant on susceptibility testing, but lack the mec gene

Abstract: ObjectivesMethicillin-resistant Staphylococcus aureus (MRSA) is an important global health problem. MRSA resistance to β-lactam antibiotics is mediated by the mecA or mecC genes, which encode an alternative penicillin-binding protein (PBP) 2a that has a low affinity to β-lactam antibiotics. Detection of mec genes or PBP2a is regarded as the gold standard for the diagnosis of MRSA. We identified four MRSA isolates that lacked mecA or mecC genes, but were still phenotypically resistant to pencillinase-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 21 publications
8
89
0
2
Order By: Relevance
“…Some researchers in Nigeria and elsewhere have also reported absence of mecA gene as well as the gene product, PBP2a or PBP2', in phenotypic MRSA strains and have suggested the possibility of hyper-production of β-lactamase as a cause of this phenomenon (11,12). We also did not test for this in our study.…”
Section: Resultsmentioning
confidence: 61%
“…Some researchers in Nigeria and elsewhere have also reported absence of mecA gene as well as the gene product, PBP2a or PBP2', in phenotypic MRSA strains and have suggested the possibility of hyper-production of β-lactamase as a cause of this phenomenon (11,12). We also did not test for this in our study.…”
Section: Resultsmentioning
confidence: 61%
“…However, other mechanisms may be involved in the expression of oxacillin resistance such as the production of a new methicillinase, change in the penicillin-binding protein subtypes, or increased levels of resistance to cadmium (Massidda et al, 2006;Park et al, 2013). It has been shown that mutations in the penicillin-binding proteins 1, 2, and 3 may lower their affinity for the β-lactam antibiotics (Ba et al, 2014), mediating oxacillin resistance in the absence of mecA or mecC. Other studies are necessary to investigate the oxacillin resistance mechanism in the 13 mecA-and blaZ-negative CNS isolates we found in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various point mutations in PBP2 and other PBPs, often in the transpeptidase domain targeted by β-lactams, have been observed in such clinical isolates (132)(133)(134)(135). There are few data on the prevalence of such isolates, but anecdotally they appear rare and their level of resistance low compared with that of mecA MRSA.…”
Section: Non-meca Gene-mediated Methicillin Resistancementioning
confidence: 99%